INITIALLY BUILDING AND APPLYING A LIST OF DRUG INTERACTIONS AT VINH LONG GENERAL HOSPITAL, IN 2020 (Vietnam Journal of Community Medicine, 2021)
Background: Drug interactions are the main causes of adverse drug events. In order to promptly detect, and handle drug interactions, medical staff often have to look up information in different databases. However, in practice this is still difficult. Stemming from practical needs, we conducted the study "Initially building and applying a list of drug interactions at Vinh Long General Hospital, in 2020".Methods: The study built a list of drug interactions appearing in the list of outpatient drugs at Vinh Long General Hospital. Then, the above list was used to examine the drug interaction on 260 outpatient prescriptions at the hospital.            Results: The main findings show that 23 pairs of interactions appearing in the outpatient drug list applied at Vinh Long General Hospital; The rate of prescriptions with interactions is still quite high (44.2%). Among prescriptions with interactions: the rate of prescriptions with 1 interaction was 58.2%; 13% of prescriptions have 3 types of interactions and 4.5% of prescriptions have more than 3 types of interactions. The proportion of prescriptions with interactions at level 1 – "need to be monitored"  accounted for 72.2%. The rate of prescriptions with serious interactions requiring replacement of other drugs was 11.3% and contraindications was 2.6%.
Keywords: Drug interactions; outpatient